Robust facial feature extraction for video coding - Phang, Chui Lian (Faculty of Computer Science and Information Technology, 2006)
Model-based coding is a good alternative traditional statistical-based techniques to deal with the bandwidth limitation in video conferencing over low speed networks. In order to apply model-based coding in real life video conferencing, robust extraction of facial features is needed